2022
DOI: 10.1002/adfm.202113280
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Therapeutic Ion‐Based Microspheres with Precise Ratio‐Controlled Delivery as Microscaffolds for In Situ Vascularized Bone Regeneration

Abstract: Therapeutic ions, such as Si and Mg, play vital roles in regulating metabolism and promoting tissue repair, hence providing an efficient strategy in tissue engineering. The regenerative outcome is strongly dependent on the targeted delivery and controlled release of therapeutic ions. Nevertheless, it remains challenging to deliver multiple ions at controlled manners and ratios. Herein, hierarchical therapeutic ion‐based microspheres are fabricated. The coordinated release of Mg and Si ions at pre‐set ratios is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 76 publications
1
25
0
Order By: Relevance
“…In a rat skull defect model, PNM2 microspheres can significantly increase the volume of regenerating vascularized new bone tissue (Figure 4D). 68 [SrCuSi 4 O 10 ] nanosheets can continuously release bioactive ions (Sr, Cu, Si), which promote the cell proliferation of HUVECs in vitro and improve vascularized bone regeneration in vivo 73 …”
Section: Application Of Biomaterials In Tissue Engineering Vasculariz...mentioning
confidence: 99%
See 2 more Smart Citations
“…In a rat skull defect model, PNM2 microspheres can significantly increase the volume of regenerating vascularized new bone tissue (Figure 4D). 68 [SrCuSi 4 O 10 ] nanosheets can continuously release bioactive ions (Sr, Cu, Si), which promote the cell proliferation of HUVECs in vitro and improve vascularized bone regeneration in vivo 73 …”
Section: Application Of Biomaterials In Tissue Engineering Vasculariz...mentioning
confidence: 99%
“…In a rat skull defect model, PNM2 microspheres can significantly increase the volume of regenerating vascularized new bone tissue (Figure 4D). 68 69 (F) The engineered exosomes encapsulate a vascular endothelial growth factor (VEGF) plasmid. Copyright permission from Zha et al 70 Angiogenic cytokines, peptides, and nucleic acids loaded on tissue-engineered scaffolds can promote the reconstruction of vascularized bone tissue.…”
Section: Promotion Of Bone Vascularization By Altering Hydrogel Loadi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these findings indicated that the PEO@SiO coating effectively promoted angiogenesis attributed to the release of Si ions. It is well established that Si has a positive effect on angiogenesis in vitro and in vivo (Mao et al, 2017;Wan et al, 2022). For example, Si doping of biomaterials is beneficial for the proliferation of HUVEC and upregulates the expression of angiogenesis-related genes (Wang et al, 2018b).…”
Section: In Vitro Performance Of the Peo@sio Coatingmentioning
confidence: 99%
“…The electrospun fibers (PLLA/Gel) are composed of poly(L-lactide) (PLLA) and gelatin (Gel), which showed excellent cell affinity and good mechanical support for cell sheets and D-ECMs as displayed in our previous research studies. [32][33][34] BMSCs are the main cells involved in the osteochondral repair via microfracture treatment in clinical therapy, 35,36 as illustrated in Scheme 1, we herein investigated the capacity of the D-ECMs secreted by BMSCs, MC3T3, Cho, and HCho to modulate the biological responses of BMSCs, followed by in vivo evaluations using a subcutaneous implantation model in rats. Promisingly, the findings of this study may lay a foundation to construct a gradient osteochondral scaffold with a D-ECMbased intermediate layer for enhanced cartilage-to-bone transition remodelling, which decides the subsequent osteochondral regeneration.…”
Section: Introductionmentioning
confidence: 99%